Trends and outcomes of chemotherapy timing in critically ill patients with hematologic malignancies using a Japanese national database - Yudai Iwasaki; Kunio Tarasawa; Tadashi Kamio; Yu Kaiho; Saori Ikumi; Shizuha Yabuki; Kiyohide Fushimi; Kenji Fujimori; Masanori Yamauchi (Scientific Reports)
Abstract Hematologic malignancies are a global public health concern, with high mortality rates in patients requiring critical care. The role of chemotherapy during intensive care unit (ICU) admission in this context remains unclear. This study aimed to analyze trends in survival rates based on chemotherapy timing and examine patient characteristics, ICU treatments, and clinical outcomes in each group. Using the Japanese Diagnosis Procedure Combination inpatient database, data from 21,837 patients aged ≥ 18 years who were hospitalized for hematologic malignancies and admitted to ICUs between April 1, 2012, and March 31, 2022, were analyzed. Patients were categorized based on chemotherapy timing as follows: no chemotherapy (NC), chemotherapy before ICU admission (CB), chemotherapy during ICU admission (CD), and chemotherapy after ICU discharge (CA). Mortality trends were assessed, with in-hospital mortality as the primary outcome variable. The CB group had the highest mortality rate, which decreased over time (61.2% in 2012 to 46.2% in 2021). The CD group had stable mortality rates (24.2% in 2012 and 22.6% in 2021), with a notable proportion of patients (55.4%) discharged home. These findings highlight the need for further investigation into the factors influencing ICU outcomes in patients receiving chemotherapy.